2021
DOI: 10.1177/20458940211059055
|View full text |Cite
|
Sign up to set email alerts
|

The association of six‐minute walk work and other clinical measures to cardiopulmonary exercise test parameters in pulmonary vascular disease

Abstract: In pulmonary vascular disease (PVD) exercise abnormalities can include reduced exercise capacity, reduced oxygen pulse (O2 pulse) and elevated VE/VCO2. The association of clinical measures such as 6 minute walk work (6MWW), haemodynamics, lung function and echocardiogram to peak VO2, O2 pulse and VE/VCO2 has not been fully investigated in PVD Aims: To determine the relationship of 6MWW and other clinical measures to peak VO2, peak O2 pulse and VE/VCO2. Additionally, to investigate the ability to predict peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(64 reference statements)
0
3
1
1
Order By: Relevance
“…The CPET is an incremental test that measures maximum or peak exercise capacity, whereas the 6MWT is usually a submaximal test since it is not incremental. Although our group demonstrated that, in patients with PH, this test represents a maximum capacity, 14 it could not be confirmed that this is the case with all the patients evaluated by Robertson et al, 1 since approximately only half of them, showed PH. It is likely the group with CTED, with a mean pulmonary artery pressure of 16 ± 6 mmHg, behaves like the rest of the population and the 6MWT is a submaximal exercise.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…The CPET is an incremental test that measures maximum or peak exercise capacity, whereas the 6MWT is usually a submaximal test since it is not incremental. Although our group demonstrated that, in patients with PH, this test represents a maximum capacity, 14 it could not be confirmed that this is the case with all the patients evaluated by Robertson et al, 1 since approximately only half of them, showed PH. It is likely the group with CTED, with a mean pulmonary artery pressure of 16 ± 6 mmHg, behaves like the rest of the population and the 6MWT is a submaximal exercise.…”
contrasting
confidence: 65%
“…Furthermore, our data showed that the response to exercise in PH patients indicates cardiovascular limitation due to increased right ventricular afterload. However, in the supplementary material shown by Robertson et al 1 notable differences in the hemodynamic profile of both populations can be seen and conclusions are not so clear.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…As informações do TCPE comprovaram o acometimento vascular pulmonar causado pela HAP primária, com repercussão cardíaca, evidenciado pela alteração do comportamento do pulso de oxigênio ao esforço, aumento significativo da relação VE/VCO2 slope, alto VE/VCO2 nadir, baixo PETCO2 pico(Guazzi, et. al., 2017;Robertson, et. al., 2021;Thirapatarapong, et.…”
unclassified